Influence of Body Conditions on Urine Production and Identification of Abnormal or Pathological Substances in the Body - Annisa Dwi Arindra (Riviera Publishing, 2025)
The background of this study is based on the importance of urine as a health indicator, which reflects the body's metabolic condition and can identify the presence of abnormal or pathological substances. Urine contains various organic and inorganic compounds that can change depending on a person's health condition, such as diabetes or pregnancy. The objective of this study is to analyze the influence of bodily conditions on urine production and to identify abnormal substances in urine using various chemical tests. The research method involves testing urine samples from healthy individuals, pregnant women, and diabetes patients using pH, chloride, sulfate, phosphate, glucose, and albumin tests. The results of the study showed significant differences in urine composition between normal and abnormal samples, such as more acidic pH in diabetic urine and the presence of glucose and protein in certain urine. The implications of this study contribute to early diagnosis and health condition monitoring through urine analysis, as well as providing a basis for the development of more accurate and efficient examination methods.